2021
DOI: 10.1172/jci135963
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipid acylation modulates plasma membrane lipid organization and insulin sensitivity in skeletal muscle

Abstract: Aberrant lipid metabolism promotes the development of skeletal muscle insulin resistance, but the exact identity of lipid-mediated mechanisms relevant to human obesity remains unclear. A comprehensive lipidomic analysis of primary myocytes from individuals that are insulin-sensitive and lean (LN) or insulin-resistant with obesity (OB) revealed several species of lysophospholipids (lyso-PL) that were differentially-abundant. These changes coincided with greater expression of lysophosphatidylcholine acyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 78 publications
6
77
0
1
Order By: Relevance
“…LXR activation promotes the entry of unsaturated fatty acids into PLs through LPCAT3, thereby reducing liver ERS and inflammation ( Rong et al, 2013 ). Patrick et al ( Ferrara et al, 2021 ) found that mice with skeletal muscle-specific knockout of LPCAT3 (LPCAT3-MKO) exhibited greater muscle lyso-PC/PC, concomitant with improved skeletal muscle insulin sensitivity. Conversely, skeletal muscle-specific overexpression of LPCAT3 (LPCAT3-MKI) promoted glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…LXR activation promotes the entry of unsaturated fatty acids into PLs through LPCAT3, thereby reducing liver ERS and inflammation ( Rong et al, 2013 ). Patrick et al ( Ferrara et al, 2021 ) found that mice with skeletal muscle-specific knockout of LPCAT3 (LPCAT3-MKO) exhibited greater muscle lyso-PC/PC, concomitant with improved skeletal muscle insulin sensitivity. Conversely, skeletal muscle-specific overexpression of LPCAT3 (LPCAT3-MKI) promoted glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Force production in extensor digitorum longus (EDL) muscle was measured as previously described. 14,18,29 Briefly, EDL muscles were sutured at each tendon and placed in a tissue bath (Aurora Scientific, Model 801C). The optimal length (L o ) of each muscle was determined by pulse stimulation.…”
Section: Skeletal Muscle Force Productionmentioning
confidence: 99%
“…14 Mice with tamoxifen-inducible skeletal muscle-specific overexpression of LPCAT3 (LPCAT3-MKI) were generated. 14 This strategy successfully yielded mice with increased LPCAT3 transcript and protein in skeletal muscle (Figures 2A and S1A). Body and fat masses were not different between the groups (Figure 2B,C).…”
Section: Skeletal Muscle-specific Overexpression Of Lpcat3 Lowers Lyso-pc and Lyso-pe Without Robustly Affecting Other Classes Of Lipidsmentioning
confidence: 99%
“…Interestingly, this LPC/PC ratio has just been proposed as a factor capable of modulating the physical properties of cell membranes and the activity of membrane receptors. Indeed, a lipidomic analysis recently performed on primary myocytes from individuals that are insulin-sensitive and lean or insulin-resistant with obesity (OB) also revealed a global phospholipidome downmodulation in OB myotubes [25]. Authors underlined the specific decrease in the LPC/PC ratio in these OB myotubes that resulted from a greater expression of lysophosphatidylcholine acyltransferase 3 (LPCAT3), an enzyme involved in phospholipid transacylation (Lands cycle).…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies suggest that altering the LPC/PC ratio of cell membranes is sufficient to disrupt the physical properties of membranes [25], we also focused on the Lyso-PL/PL ratios. Interestingly, the LPC/PC ratio is significantly decreased in OBDysG individuals when compared to OBNG patients (Figure 7).…”
Section: A Few Individual Phospholipidic Species Allow To Distinguish Obese Patients With Dysglycemia From Normoglycemic Obese Individualmentioning
confidence: 99%